THE ANALYSIS OF ABILITY TO EXPRESS THE OPINION IN THEMATIC LEARNING ON 4TH GRADE STUDENTS - Miftaqul Ika Wahyuni; Nugrananda Janattaka (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstract. This research is to describe the ability to express opinions and difficulties experienced by students to express their opinions in thematic learning on grade 4th students of SD Negeri 2 Kedungsoko. The type of research used in this research is descriptive qualitative research by collecting data using observation, interviews and documentation. The study began on March 25, 2019 until June 18, 2019 in the fourth grade students of SD Negeri 2 Kedungsoko with a total of 21 students. Based on the data analysis with five indicators of ability to express opinions, from 21 students showed that in the aspect of conformity of opinion 11 students had good abilities, aspects of fluency 9 students with good abilities, aspects of courage 9 students with good courage, aspects of clarity of opinion 7 students with good abilities, aspects of the coherent of ideas/concepts 2 students with good abilities. The ability to express opinions in thematic learning on fourth grade students of SD Negeri 2 Kedungsoko can be concluded that 12 students are still less able to express their opinions well. The difficulty experienced by students to express their opinions in thematic learning is the difficulty of expressing their opinions clearly, being unable to communicate opinions with a good language, doubts in expressing opinions, unclear voice intonation, lack of the coherent of ideas / concepts delivered. Keywords: Ability to express opinions, thematic, students.